At night all blood is black - Diop, David, 1966- (Farrar, Straus and Giroux, 2020)
"A 'Chocolat' soldier with the French army during World War I, Senegalese Alfa Ndiaye's friend Mademba Diop is in the same regiment. Injured in battle, Diop begs Alfa to kill him and spare him the pain of a long and agonizing death in No Man's Land. Unable to commit this mercy killing, madness creeps into Alfa's mind. He sees this refusal as cowardice. To avenge the death of his friend and find forgiveness for himself, every night Alfa sneaks across enemy lines to find and murder a blue-eyed German soldier, returning with the German's severed hand. As rumors circulate that Alfa is a soul-eater, how far will he go to make amends to his dead friend?"--Provided by publisher.